Gold Standards in Periodontics: A Review - Koirala, Pramod Kumar; Pradhan, Shaili (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
The field of dentistry has evolved where people expect the best oral health care from specialists. Periodontics is that specialty of dentistry which deals with prevention, diagnosis, and treatment of diseases of the supporting tissues of the teeth. Almost half of the world's population is suffering from periodontal diseases. Periodontitis is the sixth most common chronic diseases in the world and along with dental caries, the most common cause of tooth loss. Through the effort of various professional organisations and research, various reliable products and treatment modalities have been developed. A gold standard is a benchmark which has been thoroughly tested and has reputation as a reliable modality. Some of established gold standards in periodontics include: periodontal probing, measurement of clinical attachment loss, bone loss, cone beam computed tomography, quantitative polymerase chain reaction tests, biopsies as investigative techniques; periodontal debridement, subepithelial connective tissue graft for recession coverage, lasers, autogenous bone in alveolar ridge augmentation prior to oral implantation, dental implant as reconstruction of missing dentition, and chlorhexidine mouth wash as treatment options. The objective of the review is to provide critical evaluation of the data available from existing studies in Periodontics which can help identify potential research areas to explore.